2014
DOI: 10.5860/rusq.53n3.225
|View full text |Cite
|
Sign up to set email alerts
|

Looking at the “Alert Collector”

Abstract: The "Alert Collector" is one of RUSQ's most popular columns, offering selectors in both academic and public libraries starting points for developing collections focused on specific topics, subject areas, or genres. With a long-running column, it can be useful to occasionally step back, examine the premise of the column, and offer suggestions to readers who might be interested in contributing to the "Alert Collector" in the future. Here, current editor Kelly Myer Polacek and past editor Neal Wyatt collaborate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…8,9 As shown in Figure 1, the formation of a peptide bond on the surface of the ribosome during peptide elongation involves activated transfer RNAs, one bound to the ribosomal P site and bearing a peptide, and the other bound to the ribosomal A site and containing an α-amino acid. 6,10,11 While the complex that results in peptide bond formation requires both protein factors and energy, formation of the peptide bond itself does not require additional energy. Peptide bond formation can be carried out in solution but the reaction is quite slow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 As shown in Figure 1, the formation of a peptide bond on the surface of the ribosome during peptide elongation involves activated transfer RNAs, one bound to the ribosomal P site and bearing a peptide, and the other bound to the ribosomal A site and containing an α-amino acid. 6,10,11 While the complex that results in peptide bond formation requires both protein factors and energy, formation of the peptide bond itself does not require additional energy. Peptide bond formation can be carried out in solution but the reaction is quite slow.…”
Section: Introductionmentioning
confidence: 99%
“…12 The ribosome greatly accelerates this process; ribosomal peptide bond formation is estimated to be 10 5 −10 7 -fold more rapid than the uncatalyzed reaction. 10,13 In recent years, mechanisms suggested to account for ribosomal peptide bond formation have been informed by X-ray crystal structure data. Initially, it was suggested that the mechanism involved the active participation of 23S ribosomal RNA nucleotide A2451 (E. coli nomenclature used throughout) via general acid-base catalysis, as this nucleotide had been found to be in close proximity to the 3′-CCA ends of A-site and P-site tRNA substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Chloramphenicol (CAM) (Scheme 1) is an antibiotic with a wide spectrum of activity against Gram-positive and Gram-negative cocci and bacilli. 1 It is primarily bacteriostatic and works by binding to specific residues of the 23S rRNA on the 50S subunit of the bacterial ribosome, 2,3 disrupting the action of the peptidyltransferase enzyme and leading to the inhibition of important biological functions such as peptide bond formation, 4 termination of translation, 5 and translational accuracy. 6 However, treatment with CAM may be accompanied by deleterious side effects notably neurotoxicity, 7 bone marrow depletion and aplastic anemia, 8 and as a result, its use is often limited to topical ophthalmic infections and other serious infections when other suitable drugs are unavailable, such as meningitis caused by Haemophilus influenzae, Streptococcus pneumoniae, and Neisseria meningitides.…”
mentioning
confidence: 99%